2015
DOI: 10.1098/rsif.2015.0045
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent model of deformation and detachment of a biofilm under fluid flow

Abstract: A novel biofilm model is described which systemically couples bacteria, extracellular polymeric substances (EPS) and solvent phases in biofilm. This enables the study of contributions of rheology of individual phases to deformation of biofilm in response to fluid flow as well as interactions between different phases. The model, which is based on first and second laws of thermodynamics, is derived using an energetic variational approach and phase-field method. Phase-field coupling is used to model structural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 59 publications
2
46
0
Order By: Relevance
“…A previous study also suggested that protein-rich regions on the Lactobacillus johnsonii bacteria surface were stiffer than that of polysaccharide-rich regions 45 . Because stiffer biofilms may be more stable against shear stress, 16 less detachment and release of biofilm-associated pathogens in DWDS would be expected. Therefore, although long-term disinfection could not significantly remove biofilms, less detachment of stiffened biofilms is expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study also suggested that protein-rich regions on the Lactobacillus johnsonii bacteria surface were stiffer than that of polysaccharide-rich regions 45 . Because stiffer biofilms may be more stable against shear stress, 16 less detachment and release of biofilm-associated pathogens in DWDS would be expected. Therefore, although long-term disinfection could not significantly remove biofilms, less detachment of stiffened biofilms is expected.…”
Section: Discussionmentioning
confidence: 99%
“…1013 Biofilm elasticity and cohesiveness are shown to be essential for the detachment of biofilms and biofilm-associated pathogens. 1416 Therefore, comprehensive understanding of the mechanical and structural properties for drinking water biofilms will provide information to predict, assess, and aid in controlling the risk of pathogens associated with DWDS biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…(39) becomes a modified Cahn-Hilliard equation) and a free surface film state is found to form, where spinodal decomposition is a possible mechanism [330]. This approach has been extended to include EPS with an additional phase field, which reproduces the cohesive failure of biofilm under shear flow [333], and with the inclusion of a viscoelastic model of the EPS [334].…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…Continuum representations of the biofilm as constitutively linear elastic [21,26,28,92], non-linear elastic [12,27], viscous [20], or viscoelastic [95] bodies is challenging as the interface must be tracked using stress and displacement matching; simplifications such as a one-way coupling or reduced dimensionality are sometimes employed. Interface tracking is not required for phase field models, which have been employed to argue that low matrix elasticity is required for streamers to form [94] and to investigate the role of cohesion on interface stabilisation [51]. The non-overlapping range of feature sets and problems considered makes it difficult to discern a coherent picture from these modelling studies, but it is hoped that the advent of full-featured simulations (e.g.…”
Section: Fluid-structure Couplingmentioning
confidence: 99%
“…Reactor geometries are designed to expose high surface areas of the biofilm to flow, such as porous media [18,99] or fibres [47,94], and biomass effluent and other quantities measured.…”
Section: Flow Cellsmentioning
confidence: 99%